Break free from suckville : How a simple mental change will spark your performance - McCabe, Bhrett (Birmingham, AL : 606 Publishing, 2021)
"There is a myth in the competitive world that you will eventually reach your potential if you prepare correctly. Why do you leave competitions frustrated with your execution level and regret your effort if that is the case? The truth is you will never reach your potential, and the quest to create that of success and consistency in your game is destroying your mentality. The space between your possibility and the reality of your performance is what I call 'Suckville' because the struggles of falling short suck. " --Author's web site
Keywords: Sports -- Psychological aspects; Athletes -- Psychology